Usefulness of Peak Systolic Strain Measurement by Automated Function Imaging in the Prediction of Coronary Perfusion in Patients with Acute Myocardial Infarction - Cho, Jung Sun (The Korean Association of Internal Medicine, 2010)
BACKGROUND/AIMS: The usefulness of global longitudinal peak systolic strain (GLPSS) measurement by automated function imaging (AFI) in the prediction of perfusion status of infarct-related artery (IRA) before percutaneous coronary intervention (PCI) was evaluated. METHODS: Sixty-nine patients with acute myocardial infarction (AMI) who underwent successful primary PCI were divided into two groups; the patients with occlusion of IRA (Group I, 41 patients, 63.0 ± 14.9 years of age, 31 males) versus the patients with patent IRA (Group II, 28 patients, 63.8 ± 11.2 years of age, 15 males). GLPSS by AFI and wall-motion score index (WMSI) were analyzed in both groups. RESULTS: GLPSS was significantly decreased in Group I compared with Group II (-11.2 ± 3.7 vs. -14.1 ± 4.7%, p = 0.005), but WMSI (1.49 ± 0.28 vs. 1.35 ± 0.32, p = 0.062) did not differ between groups. GLPSS of infarct segments was significantly lower (-3.7 ± 5.4 vs. -11.4 ± 4.8%, p < 0.001), and WMSI of infarct segments was significantly higher (2.13 ± 0.57 vs. 1.66 ± 0.57, p = 0.001) in Group I compared with Group II. By receiver operation curve analysis, the area under the curve to predict IRA occlusion was 0.850 in GLPSS of infarct segments and 0.719 in WMSI of infarct segments. The optimal cut-off value to predict IRA occlusion was -9.4% in GLPSS of infarct segments (sensitivity, 85.4%; specificity, 67.9%) and 1.68 in WMSI of infarct segments (sensitivity, 78.0%; specificity, 60.7%). CONCLUSIONS: The present study suggested that GLPSS measured by AFI is a more sensitive predictor of IRA occlusion than is WMSI before PCI. Routine measurement of GLPSS by AFI can be a very useful tool in risk stratification of AMI.